THE APPLICATION OF PROBLEM-BASED LEARNING IN IMPROVING SPEAKING SKILL AT MADRASAH ALIYAH NEGERI 1 PALU - Zuhra, Zuhra (Fakultas tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Palu, 2016)
This research aims at investigating how to improve the speaking skill at Madrasah Aliyah Negeri 1 Palu through Problem-Based Learning. This research employed Classroom Action Research (CAR) where the subject was 22 students. The researcher and her collaborator collected the data by using observation checklists, field notes, test, and questionnaire. The data were analyzed qualitatively and quantitatively. The results showed that the application of problem-based learning techniques could improve the students’ speaking skill. In cycle 1, there were 10 students successful in speaking test and the rest were not successful. The group achievement was 45, 45% and the mean score was 67, 36%. The researcher continued to cycle 2 because the result of the speaking test in cycle 1 did not meet the criteria of achievement (50%). In cycle 2, the result revealed that there were 18 students who were successful and there were only 4 students who were not successful. The group achievement was 81, 81% and the mean score was 78, 27%. The research has been completed in cycle 2 because the result showed that the criteria of success 50% have been achieved.